Foreign language anxiety: perceptions and attitudes in the Egyptian ESL classroom - Attia, Shaden Samir (AUC Knowledge Fountain, 2015)
Foreign Language Anxiety (FLA) has been extensively researched and different variables have been investigated to determine the relationship that ties FLA with these variables. Foreign Language Anxiety affects both the learning and teaching environments and some teachers are unaware of this phenomenon and the effects it has on the learning environment and more specifically on the students learning English. The literature has shown a lack of information on Egyptian teachers' and students' perceptions of FLA. For this reason, the present study investigated FLA and teachers' perceptions and awareness of its presence in the classrooms. The relationship between students' sex and FLA and different activities used in English as Second Language (ESL) classrooms were also explored to determine the possible effects they have on FLA. A combination of quantitative and qualitative instruments was used in order to investigate the previously mentioned foci. The instruments included five interviews with teachers, six classroom observations, a survey for teachers and a questionnaire for students. The main aim of using these instruments was to collect reliable data from a diverse group of participants. The teachers' sample consisted of 49 teachers from different departments at the American University in Cairo (AUC), the School of Continuing Education (SCE) and other Egyptian universities and who have different backgrounds and years of teaching experience. The teachers taught different courses and students of different ages. The students' sample consisted of 77 students from different ages and backgrounds studying in the SCE and at AUC. The findings of the study have revealed the importance of teachers' awareness of FLA and the effects of sex and different activities on it. Some teachers are aware of the presence of Foreign Language Anxiety in the ESL classrooms. On the other hand, others believe that teachers, in general, are not aware of FLA and even when they notice anxiety they do not always relate it to the learning of a foreign or a second language. Some teachers believed FLA has negative effects on students, while others thought it can have both negative and positive effects. Teachers, however, were unaware of the effect sex has on FLA and the effect it has on different skills and on affective anxieties. Egyptian female and male students suffered from different levels of skill-specific anxiety and affective anxieties. The results have shown that both teachers and students preferred group and pair work to individual activities as they were more relaxing and less anxiety-provoking. Teachers emphasized the role of positive feedback and creating a supportive learning environment in reducing FLA. The findings highlighted the different opinions teachers and students have about the skills that are most anxiety-provoking. Most teachers believed speaking is the most anxiety-provoking skill, while students expressed having anxiety in all four skills. Students also expressed having high levels of affective anxieties, i.e. fear of negative evaluation, test anxiety, cognitive anxiety and somatic anxiety. Cognitive anxiety is a type of anxiety that has its sources from the student's mental worry and anxiety, i.e. students worrying about being corrected for every mistake by their teacher. Somatic anxiety, on the other hand, is a type of anxiety manifested through body symptoms such as the students feeling their heart pounding while using the language. These findings contribute to raising teachers' awareness of Foreign Language Anxiety in the ESL classrooms and how it correlates with different variables such as sex, specific skills and activities. They also underscore the possible effects culture could have on students and the importance of teachers' awareness of this point. Different pedagogical implications, limitations and possible future research ideas are included to aid teachers and researchers obtain a clearer understanding of this phenomenon.